Correction: Synthesis and properties of push–pull porphyrins as sensitizers for NiO based dye-sensitized solar cells. Issue 12 (28th March 2015) - Maufroy, Antoine; Favereau, Ludovic; Anne, Frédéric B.; Pellegrin, Yann; Blart, Errol; Hissler, Muriel; Jacquemin, Denis; Odobel, Fabrice
<x xml:space="preserve">Abstract</x> Correction for 'Synthesis and properties of push–pull porphyrins as sensitizers for NiO based dye-sensitized solar cells' by Antoine Maufroy et al., J. Mater. Chem. A, 2015, 3, 3908–3917.